Théologie et/ou anthropologie politique de l’« ennemi » (de Schmitt à Plessner) - Sommer, Christian (Bollettino Filosofico, 2019)
The text intends to investigate and clarify the salient aspects and limits of a possible and barely deepened relationship of proximity between H. Plessner and C. Schmitt regarding the interpretation and use of the friend/enemy-dichotomy. One of the goals is to show that, although in his text of 1931 Macht und menschliche Natur Plessner tries to ground political anthropology by explicitly referring to the friend/enemy-dichotomy as it was formulated by Schmitt, he develops this dualism in the light of the opposition between “familiar” and “foreign”. This development leads Plessner, beyond Schmitt’s aims, to the problematization of intersubjectivity. Keywords: Plessner, Schmitt, Friend/Enemy-Opposition, Political Anthropology, Intersubjectivity